ANALISIS DEBIT ALIRAN SUNGAI KAHAYAN PROVINSI KALIMANTAN TENGAH - Rendro Rismae Riady (Lambung Mangkurat University Press, 2019)
Land use in the Bereng Bengkel Kelurahan, which is downstream of the Kahayan river, tends to increase, including permanent roads on the Kahayan river bank, even though these problems have an impact on the Kahayan river environment, including landslides into the river and runoff water. Therefore there is a need for research on the Kahayan river discharge. The purpose of this research is to analyze flood discharge and water level using the Snyder HSS method and water level gauge measurement tools and analyze the Kahayan river flow phenomenon. This study uses the HEC-RAS 4.1.0 program with a flow profile simulation, to calculate the profile of a fixed and non-permanent flow water level with a return period of 5 years, 10 years, 25 years, 50 years and 100 years. Peak discharge obtained using Snyder HSS is obtained in return periods of 5 years, 10 years, 25 years, 50 years, and 100 years, amounting to 4209,558 m3 / sec, 4933,268 m3 / sec, 5627,375 m3 / sec, 5847,525 m3 / sec, and 6524,949 m3 / sec. Calibration winding in the Bereng area of ​​the Kahayan River Workshop was completed with a third-order polynomial regression equation as follows: y = -2.7103x3 + 104.48x2 - 763.96x + 1323 with a correlation value (R²) = 0.945. As for the results of using the HEC-RAS 4.1.0 program, the discharge in the return periods of 5, 10, 25, 50, and 100 years is 4100 m3 / s, 5000 m3 /, 5500 m3 / s, 6000 m3 / s, and 6500 m3 / s, with Froude number 0.11 or Fr <1 (subcritical flow).